The Role of Brand Image in Mediating the Influence of E-Wom and Product Quality on Repurchase Intention: Study on the Memories Coffee Shop in Denpasar City - Prema Atma Jaya; I Putu Gde Sukaatmadja (International Journal of Management Research and Economics, 2025)
This study aims to test and explain the role of brand image in mediating the influence of electronic word of mouth and product quality on repurchase intention of Kedai Kopi Kenangan in Denpasar City. The population used includes the people of Denpasar City who have purchased Kedai Kopi Kenangan products and the number of samples is 120 respondents using purposive sampling techniques distributed using questionnaires and analyzed using the SPSS application tool version 26.0. The results of this study indicate that electronic word of mouth has a significant positive effect on repurchase intention. Product quality has a significant positive effect on repurchase intention. Electronic word of mouth has a significant positive effect on brand image. Product quality has a significant positive effect on brand image. Brand image has a significant positive effect on repurchase intention. Electronic word of mouth has a significant positive effect on repurchase intention with brand image mediation. Product quality has a significant positive effect on repurchase intention with brand image mediation. The theoretical implications of this study provide evidence for the development of consumer behavior science and marketing management science. The practical implications of this study can be used as consideration and input for marketers at Kedai Kopi Kenangan in Denpasar City in increasing repurchase intention.